Luminescence quenching of Sm3+ ions in alkali borotellurite glasses - Tuyen, Vu Phi; Do, Phan Van (Communications in Physics, 2016)
The dependence of luminescence intensity on  Sm\(^{3 + }\) ions concentration in alkali borotellurite (ABTe) glasses has  been studied. The quenching of luminescence intensity happens  around 0.75 mol% concentration of Sm\(^{3 + }\) ions and it can relate the  energy transfer process through cross--relaxation (CR), the CR channels in  ABTe: Sm\(^{3 + }\) have been shown. The method of Van Uitert was used to find  the dominant interaction mechanism for energy transfer process.